I am David [videorecording (DVD)] - Feig, Paul; Tibber, Ben; Plowright, Joan; Caviezel, Jim, 1968-; Bonnevie, Maria, 1973-; Carinci, Viola; Holm, Anne, 1922- (Walden Media : Distributed by Lions Gate Home Entertainment, 2003)
David is a 12-year-old boy who escapes from a Communist concentration camp. He has little more with him than a compass, a sealed letter, a loaf of bread, and instructions to carry the letter to Copenhagen, Denmark. David is thrust into a world free of Communism for the first time in his young life as he travels across Europe. For David, this is a spiritual voyage of discovery, where he slowly loses his instinctual mistrust of humanity and begins to smile, share, trust and ultimately, love. Ultimately addresses the cruelties, politics, and suffering of warfare while celebrating the resilience of youth and the unbreakable spirit of a child.